PENINGKATAN PEMAHAMAN HUKUM MASYARAKAT TERHADAP SISTEM PEWARISAN ISLAM DI DESA LAOSU JAYA KABUPATEN KONAWE - Sahrina Safiuddin; Wa Ode Zuliarti; Haris Yusuf; Idris Saputra (Universitas Halu Oleo, 2023)
The goal of this community service activity is to increase the Muslim community's legal understanding of the importance of understanding the rules of the Islamic inheritance system. This activity was carried out using a direct approach method, with the entire team including students who were directly related to the community by conducting socialization or counselling while still adhering to health protocols such as keeping a distance and not gathering the community in large numbers. Based on the outcomes of the Community Service (PKM) activities carried out in Laosu Jaya Village, Konawe Regency, it can be concluded that there were still many participants present who did not fully comprehend the Islamic inheritance system, so the PKM team provided direct counselling regarding the basic principles of the Islamic inheritance system. Islamic inheritance, including: a) Definition of Islamic inheritance, b) Rights related to inheritance, c) Pillars and terms of inheritance, d) Those who are hindered in inheriting, e) Class of heirs according to the Islamic inheritance system.